Kappa-carrageenan / Zein / ZIF-8 (at) Thy composite membrane as well as preparation method and application thereof
Through the chemical crosslinking of κ-carrageenan/Zein/ZIF-8@Thy composite membrane, the problem of poor compatibility between hydrophobic protein and hydrophilic polysaccharide is solved, and efficient water absorption, antioxidant and long-term antibacterial properties are achieved. Ensure the stability and biosafety of food plastic wrap.
Patent Information
- Application Number
- CN202411321367.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
There is a problem of poor interface compatibility between hydrophobin and hydrophilic polysaccharide in the composite membrane, resulting in unstable performance and potential health risks.
采用κ-卡拉胶/Zein/ZIF-8@Thy复合膜,通过ZIF-8@Thy与天然聚合物κ-卡拉胶和玉米醇溶蛋白Zein的化学交联,提高界面相容性,并利用ZIF-8的2D层状结构和Thy的抗菌特性,实现长效抗菌性能。
It improves water absorption, antioxidant and antibacterial properties, ensures the stability and biosafety of food plastic wrap, and avoids the potential risks of traditional plastic film to the environment and health.
Smart Images

Figure CN119192689A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of biocomposite membranes, and specifically relates to a κ-carrageenan / Zein / ZIF-8@Thy composite membrane and a preparation method and application thereof. Background Art
[0002] Food cling film is a commonly used food packaging material, mainly used to cover food to keep it fresh and extend its shelf life. Common food cling films are mostly plastic products made of polyethylene (PE), polypropylene (PP), polyvinyl chloride (PVC) and other materials. These materials are petroleum-based products, not easy to degrade, causing long-term pollution to the environment, and the plasticizers in PVC cling film may penetrate into food, posing a potential risk to human health. At the same time, some cling films have insufficient barrier properties against oxygen, moisture and other gases, causing food to easily deteriorate.
[0003] In recent years, for the purpose of environmental protection, various natural biopolymers such as proteins, polysaccharides, and lipids have been widely used in the preparation of food packaging materials. The films made of these natural biopolymers are biodegradable, non-toxic, and reduce environmental pollution. Compared with the films prepared from lipids or polysaccharides alone, composite films, especially composite films of polysaccharides and proteins, are unique due to their excellent gas barrier and biosafety and environmental protection performance.
[0004] In the composite film of polysaccharide and protein, hydrophobic protein is often used. The addition of hydrophobic protein can enhance the barrier property of the plastic wrap to moisture and oxygen, thereby extending the shelf life of food. However, polysaccharides contain a large number of hydroxyl (-OH) functional groups, showing hydrophilicity. There is a problem of poor interfacial compatibility between hydrophobic protein and hydrophilic polysaccharides, which may lead to unstable performance of the composite material. In order to solve this problem, plasticizers (such as polyethylene glycol, glycerol, etc.) are often added in the prior art. These plasticizers may also penetrate into food, posing potential risks to human health, such as nephrotoxicity, allergic reactions and cytotoxicity. Summary of the invention
[0005] 1. Problem to be solved
[0006] In order to solve the problem of poor interface compatibility between hydrophobic proteins and hydrophilic polysaccharides in composite membranes, the present application provides a κ-carrageenan / Zein / ZIF-8@Thy composite membrane and a preparation method and application thereof. The addition of ZIF-8@Thy can effectively improve the interface compatibility of the κ-carrageenan / Zein composite membrane, and improve the water absorption and antioxidant properties. At the same time, ZIF-8 is a sustained-release platform for drugs, which is sensitive to pH. The slow release of drugs from the metal frame can have long-term antibacterial effects, and therefore has stable long-term antibacterial properties.
[0007] 2. Technical solution
[0008] In order to solve the above problems, the technical solutions adopted in this application are as follows:
[0009] The present application provides a κ-carrageenan / Zein / ZIF-8@Thy composite membrane, the main components of which include: κ-carrageenan, Zein and ZIF-8@Thy, wherein:
[0010] κ-Carrageenan is a natural polysaccharide, which is considered safe and reliable for use in food by the World Health Organization and the Food and Agriculture Organization of the United Nations.
[0011] Zein is a hydrophobic corn protein, which is classified as safe (GRAS) by the U.S. Food and Drug Administration (FDA);
[0012] Thy is thymol (Thymol, 2-isopropyl-5-methylphenol, C 10 H 14 Thymol (also known as thymol) is a phenolic monoterpene that is mainly found in species of the genus Thymus. It has excellent antioxidant, anti-inflammatory, antibacterial and antifungal properties. It has been included in the GRAS food additive list by the European Union (EU) and the U.S. Food and Drug Administration (FDA) and is considered to be a safe and non-toxic antibacterial agent and antioxidant.
[0013] ZIF-8 is a zeolite imidazolate framework-8 (composed of 2-dimethylimidazole and Zn 2+ Composition), is a metal organic framework (MOFs), which exhibits excellent chemical stability and negligible cytotoxicity; it has excellent chemical functionality and can chemically cross-link with the active groups on the natural polymer κ-carrageenan and zein, making it a good interfacial lubricant between the hydrophilic natural polymer and the hydrophobic zein; in addition, ZIF-8 shows large pores between its unique 2D layered structure, allowing it to highly load the antibacterial agent Thy and allow precise control of its release, providing more effective delivery characteristics for the antibacterial agent, and has excellent antioxidant and antibacterial properties, thereby enhancing the stability and bioavailability of the antibacterial agent.
[0014] The present application also provides a method for preparing the above-mentioned κ-carrageenan / Zein / ZIF-8@Thy composite membrane, which is prepared based on an ultrasound-assisted heating casting method and specifically comprises the following steps:
[0015] S1, dissolving dimethylimidazole and Thy in methanol and stirring until completely dissolved to obtain a dimethylimidazole / Thy solution;
[0016] S2, dissolving zinc nitrate in methanol and stirring until completely dissolved to obtain a zinc nitrate solution;
[0017] S3, adding the zinc nitrate solution dropwise to the dimethylimidazole / Thy solution, stirring, collecting the precipitate by centrifugation, washing the precipitate with methanol, and vacuum drying to obtain ZIF-8@Thy powder;
[0018] S4, heating and stirring κ-carrageenan in deionized water until it is completely dissolved to obtain a κ-carrageenan solution; then adding ZIF-8@Thy powder and heating and stirring to make it evenly dispersed, and ultrasonically degassing to obtain a reaction system 1;
[0019] S5, dissolving Zein in ethanol and stirring until completely dissolved to obtain a Zein solution;
[0020] S6, adding Zein solution dropwise to the reaction system 1 to obtain the reaction system 2;
[0021] S7, after ultrasonic degassing, pour the reaction system 2 into a flat plate to obtain a composite system flat plate;
[0022] S8, drying the composite system plate at 40-60° C. to form a κ-carrageenan / Zein / ZIF-8@Thy composite membrane.
[0023] Furthermore, the κ-carrageenan / Zein / ZIF-8@Thy composite film is stored in a constant temperature and humidity environment.
[0024] Furthermore, the constant temperature and humidity environment is 4°C and 50-60°C in humidity.
[0025] Furthermore, in the above S1, the mass ratio of dimethylimidazole to Thy should be between 20:1 and 30:1.
[0026] Furthermore, in the above S1, the stirring condition is stirring at a speed of 500 to 600 rpm.
[0027] Furthermore, in the above S1, the purity of methanol should be no less than 98%.
[0028] Furthermore, in the above S2, the concentration of zinc nitrate should be between 15 and 20 mg / mL.
[0029] Furthermore, in the above S2, the stirring condition is stirring at a speed of 500 to 600 rpm.
[0030] Furthermore, in the above S2, the purity of methanol should be no less than 98%.
[0031] Furthermore, in the above S3, the mass ratio of dimethylimidazole to zinc nitrate should be between 6:1 and 8:1.
[0032] Furthermore, in the above S3, the stirring condition is stirring at a speed of 500 to 600 rpm.
[0033] Furthermore, in the above S3, the stirring time is 24 to 48 hours.
[0034] Furthermore, in the above S3, the centrifugal conditions are: 10000-12000 rpm; and the centrifugal time is 10-15 min.
[0035] Furthermore, in the above S3, the cleaning includes using 20 to 30 mL of methanol for 2 to 3 times.
[0036] Furthermore, in the above S4, the mass concentration of the κ-carrageenan solution is 7.5-10 mg / mL.
[0037] Furthermore, in the above S4, the temperature of heating and stirring is 40 to 60°C.
[0038] Furthermore, in the above S4, the heating and stirring is carried out at a speed of 500 to 600 rpm.
[0039] Furthermore, in the above S4, the mass ratio of κ-carrageenan to ZIF-8@Thy is 1:0.5-0.1.
[0040] Furthermore, in the above S4, the mass ratio of κ-carrageenan to ZIF-8@Thy is 1:0.2-0.1.
[0041] Furthermore, the mass ratio of the above-mentioned κ-carrageenan to ZIF-8@Thy is 1:0.1, 1:0.15 or 1:0.2.
[0042] Furthermore, in the above S4, the ultrasonic condition is 35 to 45 KHz. Furthermore, in the above S4, the ultrasonic condition is 40 KHz.
[0043] Furthermore, in the above S4, the ultrasonic degassing time is 25 to 30 minutes.
[0044] Furthermore, in the above S5, the concentration of Zein is 7.5 to 10 mg / mL.
[0045] Furthermore, in the above S5, the stirring condition is stirring at a speed of 500 to 600 rpm.
[0046] Furthermore, in the above S5, the ethanol concentration is 75-85%.
[0047] Furthermore, in the above S6, the mass ratio of κ-carrageenan to Zein is 1:0.5 to 0.1. Furthermore, the mass ratio of κ-carrageenan to Zein is 1:0.25.
[0048] Furthermore, in the above S7, the ultrasonic condition is 35 to 45 KHz. Furthermore, in the above S7, the ultrasonic condition is 40 KHz.
[0049] Furthermore, in the above S7, the ultrasonic degassing time is 25 to 30 minutes.
[0050] Furthermore, in the above S8, the standing time is 25 to 30 minutes.
[0051] Furthermore, in the above S8, the drying time is 12 to 24 hours.
[0052] The present application also provides the use of the above-mentioned κ-carrageenan / Zein / ZIF-8@Thy composite film or its preparation method as a food preservative film.
[0053] The present application also provides the use of the above-mentioned κ-carrageenan / Zein / ZIF-8@Thy composite film or its preparation method in the preparation of food preservative film.
[0054] 3. Beneficial effects
[0055] Compared with the prior art, the present application has the following beneficial effects:
[0056] (1) The present application provides a κ-carrageenan / Zein / ZIF-8@Thy composite membrane and its preparation method and application. The composite membrane is a κ-carrageenan / Zein / ZIF-8@Thy composite membrane synthesized from hydrophilic polysaccharide (κ-carrageenan), hydrophobic protein (zein) and drug-loaded metal organic framework (ZIF-8) as raw materials; ZIF-8@Thy is chemically cross-linked with the active groups on the natural polymer κ-carrageenan and zein, making it a good interface lubricant between the hydrophilic natural polymer and the hydrophobic zein, thereby improving the interface compatibility between κ-carrageenan and Zein.
[0057] (2) The present application provides a κ-carrageenan / Zein / ZIF-8@Thy composite membrane and its preparation method and application. The composite membrane not only has excellent water absorption and antioxidant properties, but also has the ability to increase the loading capacity of alcohol-soluble drugs and the stability of antibacterial agents by adding metal frame ZIF-8 to the composite membrane. Moreover, ZIF-8 is a sustained-release platform for drugs, which is sensitive to pH. The drugs slowly released from the metal frame can have long-term antibacterial effects, thus having stable long-term antibacterial properties. At the same time, it has the ability to quickly release antibacterial drugs under acidic conditions.
[0058] (3) The present application provides a κ-carrageenan / Zein / ZIF-8@Thy composite film and its preparation method and application. Compared with traditional plastic polymer composite materials, κ-carrageenan / Zein / ZIF-8@Thy has better biosafety and degradability.
[0059] (4) The present application provides a κ-carrageenan / Zein / ZIF-8@Thy composite membrane and its preparation method and application. The preparation is based on an ultrasound-assisted method, which can make the ZIF-8 nanoparticles loaded with antibacterial drugs added between κ-carrageenan and Zein uniformly dispersed inside, ensuring that a composite membrane with uniform tissue distribution is obtained after casting.
[0060] (5) The κ-carrageenan / Zein / ZIF-8@Thy composite film provided in the present application and its preparation method and application have the advantages of mild synthesis method, low material cost and low requirements for synthesis equipment. Compared with the traditional PVC composite film, it has long-lasting antibacterial properties. The composite film components are safe and pollution-free to the environment and have high safety to organisms. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 The results of scanning electron microscopy observations, wherein: A is unloaded ZIF-8 (ZIF-8 powder), B and C are the cross-section and surface of the κ-carrageenan / Zein composite membrane (κc / Zein) in Comparative Example 1, D is drug-loaded ZIF-8 (ZIF-8@Thy), and E and F are the cross-section and surface of the κ-carrageenan / Zein / ZIF-8@Thy (30 mg) composite membrane in Example 1.
[0062] Figure 2 This is the infrared spectrum of each component in the κ-carrageenan / Zein / ZIF-8@Thy (30 mg) composite film in Example 1.
[0063] Figure 3 These are the cross-sectional thickness test results of the κ-carrageenan / Zein in Comparative Example 1, the κ-carrageenan / Zein / ZIF-8 composite membrane in Comparative Example 2, the κ-carrageenan / Zein / ZIF-8@Thy (30 mg) composite membrane in Example 1, the κ-carrageenan / Zein / ZIF-8@Thy (45 mg) composite membrane in Example 2, and the κ-carrageenan / Zein / ZIF-8@Thy (60 mg) composite membrane in Example 3.
[0064] Figure 4 These are the dissolution rate test results of the κ-carrageenan / Zein in Comparative Example 1, the κ-carrageenan / Zein / ZIF-8 composite membrane in Comparative Example 2, and the κ-carrageenan / Zein / ZIF-8@Thy (30 mg) composite membrane in Example 1 in water.
[0065] Figure 5These are the swelling rate test results of the κ-carrageenan / Zein in Comparative Example 1, the κ-carrageenan / Zein / ZIF-8 composite membrane in Comparative Example 2, and the κ-carrageenan / Zein / ZIF-8@Thy composite membrane in Examples 1 to 3.
[0066] Figure 6 These are the antioxidant activity test results of the κ-carrageenan / Zein in Comparative Example 1, the κ-carrageenan / Zein / ZIF-8 composite membrane in Comparative Example 2, and the κ-carrageenan / Zein / ZIF-8@Thy (30 mg) composite membrane in Example 1.
[0067] Figure 7 These are the test results of the release ability of Thy in the κ-carrageenan / Zein / ZIF-8@Thy (30 mg) composite film in Example 1 in PBS of different pH values.
[0068] Figure 8 These are the minimum inhibitory concentration test results of the same components in the κ-carrageenan / Zein / ZIF-8@Thy composite membranes in Examples 1 to 3: ZIF-8, Thy, and ZIF-8@Thy.
[0069] Fig. 9 These are the biosafety test results of the κ-carrageenan / Zein in Comparative Example 1, the κ-carrageenan / Zein / ZIF-8 composite membrane in Comparative Example 2, and the κ-carrageenan / Zein / ZIF-8@Thy (30 mg) composite membrane in Example 1.
[0070] Fig.10 These are the antibacterial tests and comparison results of the bacterial blank experimental group, the κ-carrageenan / Zein in comparative example 1, the κ-carrageenan / Zein / ZIF-8 composite membrane in comparative example 2, and the κ-carrageenan / Zein / ZIF-8@Thy (30 mg) composite membrane in example 1.
[0071] Fig.11 The results of κ-carrageenan / Zein / ZIF-8@Thy composite film applied to blueberry preservation. DETAILED DESCRIPTION
[0072] The present application is further described below in conjunction with specific embodiments.
[0073] It should be noted that the terms such as "upper", "lower", "left", "right", "middle", etc. cited in this specification are only for the convenience of description and are not used to limit the scope of implementation. Changes or adjustments to their relative relationships should be regarded as the scope of implementation of this application without substantially changing the technical content.
[0074] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.
[0075] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0076] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. The degree of flexibility for a particular variable can be easily determined by one skilled in the art.
[0077] As used herein, the term "at least one of" is intended to be synonymous with "one or more of." For example, "at least one of A, B, and C" expressly includes only A, only B, only C, and combinations of each thereof.
[0078] Concentration, amount and other numerical data can be presented in range format herein.It should be understood that such range format is only used for convenience and simplicity, and should be flexibly interpreted as not only including the numerical value clearly described as range limit, but also including all single numerical values or sub-ranges contained in the range, just as each numerical value and sub-range are clearly described.For example, the numerical range of about 1 to about 4.5 should be interpreted as not only including the limit value of 1 to about 4.5 clearly described, but also including single numerals (such as 2,3,4) and sub-ranges (such as 1 to 3,2 to 4, etc.).The same principle is applicable to the scope of only narrating a numerical value, such as "less than about 4.5", which should be interpreted as including all the above-mentioned values and ranges.In addition, no matter how the breadth of the described range or feature is, this explanation should be applicable.
[0079] Example 1
[0080] This embodiment provides a κ-carrageenan / Zein / ZIF-8@Thy composite film and a preparation method thereof.
[0081] A κ-carrageenan / Zein / ZIF-8@Thy composite membrane, comprising κ-carrageenan, Zein, ZIF-8 and Thy, has pH responsiveness and sustained antibacterial properties.
[0082] The preparation of κ-carrageenan / Zein / ZIF-8@Thy composite membrane based on ultrasound assistance specifically includes the following steps:
[0083] (1) 983 mg of dimethylimidazole and 40 mg of Thy were dissolved in 40 mL of methanol and stirred with a magnetic stirrer at 600 rpm for 30 min until completely dissolved to obtain a dimethylimidazole / Thy solution;
[0084] (2) dissolving 156 mg of zinc nitrate in 10 mL of methanol and stirring with a magnetic stirrer at 600 rpm for 30 min until completely dissolved to obtain a zinc nitrate solution;
[0085] (3) The zinc nitrate solution was added dropwise to the dimethylimidazole solution / Thy, stirred at 600 rpm for 24 h using a magnetic stirrer, and the precipitate was collected by centrifugation at 12000 rpm for 15 min, and the precipitate was washed 2 to 3 times with 30 mL of methanol and vacuum dried for 24 h to obtain ZIF-8@Thy powder;
[0086] (4) 300 mg of κ-carrageenan was dissolved in 40 mL of deionized water, heated to 40-60° C. and stirred on a magnetic stirrer (600 rpm) for 30 min until completely dissolved to obtain a κ-carrageenan solution; then 30 mg of ZIF-8@Thy powder was added and heated and stirred to make it uniformly dispersed, and ultrasonic (40 KHz) degassing was performed for 30 min to obtain a reaction system 1;
[0087] (5) 75 mg of Zein was dissolved in 10 mL of ethanol and stirred with a magnetic stirrer (600 rpm) for 30 min until completely dissolved to obtain a Zein solution;
[0088] (6) Add 10 mL of Zein solution dropwise to reaction system 1 to obtain reaction system 2;
[0089] (7) Degas the reaction system by ultrasonication (40 kHz) for 30 min and then pour it into a plate to obtain a composite system plate;
[0090] (8) The composite system plate was allowed to stand for 30 minutes and then dried in a water-tight incubator at 40-60°C for 12 hours to form a κ-carrageenan / Zein / ZIF-8@Thy composite film (κc / Zein / ZIF-8@Thy 30 mg). The κ-carrageenan / Zein / ZIF-8@Thy composite film was stored in a constant temperature and humidity environment at 4°C and 50-60°C for use.
[0091] Example 2
[0092] This embodiment provides a κ-carrageenan / Zein / ZIF-8@Thy composite film and a preparation method thereof.
[0093] A κ-carrageenan / Zein / ZIF-8@Thy composite membrane, comprising κ-carrageenan, Zein, ZIF-8 and Thy, has pH responsiveness and sustained antibacterial properties.
[0094] Based on the ultrasound-assisted preparation of κ-carrageenan / Zein / ZIF-8@Thy composite membrane, refer to Example 1, specifically, 45 mg of ZIF-8@Thy powder is added in step (4) to obtain κ-carrageenan / Zein / ZIF-8@Thy composite membrane (κc / Zein / ZIF-8@Thy45mg).
[0095] Example 3
[0096] This embodiment provides a κ-carrageenan / Zein / ZIF-8@Thy composite film and a preparation method thereof.
[0097] A κ-carrageenan / Zein / ZIF-8@Thy composite membrane, comprising κ-carrageenan, Zein, ZIF-8 and Thy, has pH responsiveness and sustained antibacterial properties.
[0098] Based on ultrasound-assisted preparation of κ-carrageenan / Zein / ZIF-8@Thy composite membrane, refer to Example 1, specifically, 60 mg of ZIF-8@Thy powder is added in step (4) to obtain κ-carrageenan / Zein / ZIF-8@Thy composite membrane (κc / Zein / ZIF-8@Thy 60 mg).
[0099] Comparative Example 1
[0100] This embodiment provides a κ-carrageenan / Zein composite film (κc / Zein) and a preparation method thereof. The preparation method comprises:
[0101] (1) dissolving 300 mg of κ-carrageenan in 40 mL of deionized water, heating to 40-60° C. and stirring on a magnetic stirrer (600 rpm) until completely dissolved to obtain a κ-carrageenan solution;
[0102] (2) 75 mg of Zein was dissolved in 10 mL of ethanol and stirred on a magnetic stirrer (600 rpm) for 30 min until completely dissolved to obtain a Zein solution;
[0103] (3) Slowly adding 10 mL of Zein solution dropwise to the κ-carrageenan solution to obtain a reaction system;
[0104] (4) Degassing the reaction system by ultrasonication (40 kHz) for 30 min and pouring it into a plate to obtain a composite system plate;
[0105] (5) After the composite system plate was allowed to stand for 30 minutes, it was allowed to stand and dry in a water-tight incubator (40-60° C.) for 12 hours to form a κ-carrageenan / Zein composite film (κc / Zein); the κ-carrageenan / Zein composite film was stored in a constant temperature and humidity environment at 4° C. and 50-60° C. for use.
[0106] Comparative Example 2
[0107] This embodiment provides a κ-carrageenan / Zein / ZIF-8 composite membrane (κc / Zein / ZIF-8) and a preparation method thereof. The preparation method comprises:
[0108] (1) Dissolve 983 mg of dimethylimidazole in 40 mL of methanol and stir with a magnetic stirrer (600 rpm) for 30 min until completely dissolved to obtain a dimethylimidazole solution;
[0109] (2) dissolving 156 mg of zinc nitrate in 10 mL of methanol and stirring with a magnetic stirrer (600 rpm) for 30 min until completely dissolved to obtain a zinc nitrate solution;
[0110] (3) The zinc nitrate solution was added dropwise to the dimethylimidazole solution, stirred with a magnetic stirrer (600 rpm) for 24 h, and the precipitate was collected by centrifugation at 12000 rpm for 15 min. The precipitate was washed 2 to 3 times with 30 mL of methanol and vacuum dried for 24 h to obtain ZIF-8 powder;
[0111] (4) 300 mg of κ-carrageenan was dissolved in 40 mL of deionized water, heated to 40-60° C. and stirred on a magnetic stirrer (600 rpm) for 30 min until completely dissolved to obtain a κ-carrageenan solution; then 30 mg of ZIF-8 powder was added and heated and stirred until it was uniformly dispersed, and ultrasonic (40 KHz) degassing was performed for 30 min to obtain a reaction system 1;
[0112] (5) Dissolve 75 mg of Zein in 10 mL of ethanol and stir on a magnetic stirrer (600 rpm) for 30 min until completely dissolved to obtain a Zein solution;
[0113] (6) Add 10 mL of Zein solution dropwise to reaction system 1 to obtain reaction system 2;
[0114] (7) Degas the reaction system by ultrasonication (40 kHz) for 30 min and then pour it into a plate to obtain a composite system plate;
[0115] (8) After the composite system plate is allowed to stand for 30 minutes, it is allowed to stand and dry in a water-tight incubator at 40-60° C. to form a κ-carrageenan / Zein / ZIF-8 composite film; the κ-carrageenan / Zein / ZIF-8 composite film is stored in a constant temperature and humidity environment at 4° C. and 50-60° C. for future use.
[0116] Example 4
[0117] This example provides a study on the physical and chemical properties of the composite films prepared in Examples 1 to 3 and Comparative Examples 1 to 2. Specifically, it includes:
[0118] (1) Microstructure characterization
[0119] Field emission scanning electron microscopy was used to characterize the morphology of unloaded ZIF-8 (ZIF-8 powder), Thy-loaded ZIF-8 (ZIF-8@Thy) and composite films containing ZIF-8. The composite film was cut, the cross section was pasted to the side of the electron microscope table with the cross section facing up, and fixed with conductive glue. After the treated composite film was placed on the gold spraying table and gold was sprayed, the microscopic morphology of the film cross section was observed and analyzed using a scanning electron microscope.
[0120] The chemical composition of each component in the composite film was determined by Fourier transform infrared spectrometer. The measurement wavelength was 4000~400nm -1 Measurements are made with a resolution of 4cm -1 .
[0121] All measurements were performed at 25°C.
[0122] Result analysis:
[0123] Scanning electron microscopy results Figure 1As shown, it can be seen that the size of the ZIF-8 nanoparticles in Figure (A) is 50-60nm, the morphology is a relatively regular polyhedron, and the size is relatively uniform; the morphology of the ZIF-8 nanoparticles loaded with Thy in Figure (D) is not much different from that of the unloaded ZIF-8 nanoparticles, which shows that loading Thy does not change the morphology of the ZIF-8 nanoparticles. Figures (B) and (E) are cross-sections of κ-carrageenan / Zein composite membranes and κ-carrageenan / Zein / ZIF-8@Thy composite membranes, respectively. It can be seen that the cross-section of Figure (E) has white dots of ZIF-8@Thy evenly dispersed in it. Figure (C) and Figure (F) show the surface of κ-carrageenan / Zein composite film and κ-carrageenan / Zein / ZIF-8@Thy composite film. It can be seen that the surface of the composite film with ZIF-8@Thy added is smoother than that of the κ-carrageenan / Zein composite film, which indicates that the addition of ZIF-8@Thy can effectively improve the interfacial compatibility of the κ-carrageenan / Zein composite film. With the disappearance of these gaps, the κ-carrageenan / Zein / ZIF-8@Thy composite film has better gas barrier properties than the κ-carrageenan / Zein composite film.
[0124] The components and infrared spectra of κ-carrageenan / Zein / ZIF-8@Thy composite membrane are shown in Figure 2. Figure 2 As shown in the spectra of ZIF-8 and ZIF-8@Thy, it can be found that 3140 cm -1 、2935.5cm -1 、1586.5cm -1 The absorption peak at 3162.5cm is the stretching of aromatic CH bonds, aliphatic CH bonds and CN bonds in 2-methylimidazole; in the spectrum of Thy, the absorption peak at 3162.5cm -1 The peak at 2962cm is the characteristic absorption band corresponding to the OH vibration of Thy. -1 and 2871.5cm -1 The absorption peaks at 1246.5~1750cm are the asymmetric and symmetric CH stretching vibrations of methyl groups. -1 The absorption peak at 550-1250cm corresponds to the C=C stretching vibration, OH plane bending vibration and CO stretching vibration of the benzene ring. -1 The absorption peaks at 3200-3500cm correspond to the inward and outward bending vibrations of the CH plane; Zein at 3200-3500cm -1 There is a broad characteristic absorption peak, which is caused by the stretching vibration of hydrogen bonds and -OH bonds within the molecule; in the infrared spectrum of κ-carrageenan, 3455.4cm -1 The characteristic absorption peak at 2926 cm -1 The peak at 1247 cm is caused by CH stretching vibration.-1 The absorption peak at about 927 cm is due to the S=O stretching vibration of sulfate ester. -1 The peak at 1537.2 cm was attributed to 3,6-galactose; while the peak at 1537.2 cm was attributed to 3,6-galactose; -1 The characteristic peaks that appeared indicate the successful combination of the two. The spectrum of κ-carrageenan / Zein film with ZIF-8 added shows that the peak of κ-carrageenan is 1541.5 cm -1 The -NH2 bond at 1646.2 cm -1 The -C=O bond at -1 and 1649cm -1 These results indicate that using ZIF-8@Thy as a bridge can improve the interfacial compatibility of κ-carrageenan and Zein.
[0125] (2) Thickness of composite film
[0126] The thickness of the composite film samples of each embodiment and comparative example was measured using a spiral micrometer. The composite film was cut into strips of 1.0 cm × 5.0 cm, and then different parts of the strips were measured using a spiral micrometer. Each piece was measured at least 5 times to ensure the accuracy of the data.
[0127] Result analysis:
[0128] Test results such as Figure 3 As shown, the thickness of the composite membranes of the embodiments and comparative examples are 0.026 mm (Comparative Example 1), 0.027 mm (Comparative Example 2), 0.027 mm (Example 1), 0.027 mm (Example 2) and 0.028 mm (Example 3), respectively. For Comparative Example 2 in which ZIF-8 was added and Examples 1 to 3 with different masses of ZIF-8@Thy, compared with Comparative Example 1, the effect of the metal frame ZIF-8 on the composite membrane is not significant, which may be because the synthesized composite membrane is relatively thin.
[0129] (3) Dissolution rate of composite film
[0130] The dried composite membrane was cut into strips of 1.0 cm × 5.0 cm and weighed and recorded (M0), placed in a beaker of 50 mL deionized water and soaked for 30 min, then removed to remove surface free water, placed in an oven at 40-50 ° C to dry completely and weighed and recorded (M1), and the solubility of the composite membrane in water was calculated. The solubility of the composite membrane was calculated by the following formula: SO = (M1-M0) / M0×100%.
[0131] Result analysis:
[0132] Test results such as Figure 4As shown, compared with Comparative Example 1, the water solubility of Comparative Example 2 and Example 1 has increased, because κ-carrageenan is a water-soluble polysaccharide with more hydrophilic groups on the molecular chain, resulting in increased water solubility. When the entire composite film is soaked in water, the cross-linking ability of κ-carrageenan with the hydrophobic protein Zein and the metal framework ZIF-8, ZIF-8@Thy becomes poor, which also makes the composite film easier to absorb water and swell or even dissolve.
[0133] (4) Swelling rate of composite membrane
[0134] The dried composite membrane was cut into strips of 1.0 cm × 5.0 cm and weighed and recorded (M0), soaked in a beaker of 50 mL deionized water for 60 min, suspended in the air for 60 s, free water on the surface was removed and weighed (M1), and the swelling degree was calculated according to the formula SW = (M1-M0) / M0×100%.
[0135] Result analysis:
[0136] Test results such as Figure 5 As shown, the swelling rates of the embodiments and comparative examples are very high, among which the swelling rates of comparative examples 1 and 2 are 2260% and 1951% respectively, and the swelling rates of examples 1 to 3 are 1944%, 1932% and 1919% respectively. This is because the composite film contains a large proportion of hydrophilic polysaccharide κ-carrageenan, and the water absorption of the composite film increases due to the combination of κ-carrageenan and water. Compared with the simple κ-carrageenan / Zein composite film, the swelling rates of comparative example 2 and examples 1 to 3 with the addition of ZIF-8 are lower, because the metal skeleton ZIF-8 is cross-linked with κ-carrageenan and Zein by hydrogen bonds during the reaction, which is reflected in the Fourier infrared spectrum. The swelling rate of Comparative Example 2 is slightly larger than that of Example 1. This is because the ZIF-8 in Example 1 is loaded with Thy, wherein Thy is electrostatically adsorbed on the surface of ZIF-8, and Thy is hydrogen-bonded with κ-carrageenan and Zein in the composite membrane, thereby reducing the swelling rate of the composite membrane. The swelling rates of Examples 2 and 3 in the figure also confirm this result.
[0137] (5) Antioxidation of composite films
[0138] 40 mg of κ-carrageenan / Zein and κ-carrageenan / Zein composite films containing ZIF-8 and ZIF-8@Thy were ground and immersed in 5 mL of 100 μmol / L DPPH in a dark environment for 1 h, and then the absorbance at 517 nm was measured. The DPPH scavenging activity was calculated by the equation:
[0139] DPPH free radical scavenging rate (%) = (Ac-As) / Ac×100%;
[0140] Wherein, Ac is the absorbance value of the control group without any sample, and As is the absorbance of the sample with DPPH methanol solution and the sample. All samples were measured three times.
[0141] Result analysis:
[0142] Test results such as Figure 6 As shown, Comparative Examples 1 and 2 have basically no obvious antioxidant activity, because polysaccharides, proteins and ZIF-8 do not have antioxidant activity. However, because Example 1 contains ZIF-8@Thy, its antioxidant activity is greatly improved compared with Comparative Examples 1 and 2, because Thy has a strong antioxidant activity. Example 1, i.e., the κ-carrageenan / Zein / ZIF-8@Thy composite film, has a strong antioxidant activity, which can not only give the composite film itself antioxidant ability, but also effectively inhibit food decay as food packaging and extend the shelf life of food.
[0143] (6) Release curves of Thy in composite films under different conditions
[0144] The release curve of Thy in the composite membrane in PBS buffer with different pH was evaluated. The composite membrane was immersed in PBS solution with different pH (pH = 4.5 / 7.4). 2 mL of supernatant was collected at specific time intervals (1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 24, 36 h) of the reaction system (the 2 mL removed was supplemented with fresh PBS), and the absorbance of the supernatant at λ = 265 nm was measured by ultraviolet spectrophotometer after centrifugation to evaluate the amount of Thy released.
[0145] Result analysis:
[0146] Test results such as Figure 7 As shown in the figure, when pH = 7.4, Thy in the κ-carrageenan / Zein / ZIF-8@Thy (30 mg) composite film is slowly released, and the cumulative release rate of Thy is about 28.77% at 5h, and its cumulative release rate reaches 37.20% at 36h; when pH = 4.5, the release rate of Thy within 5h is significantly faster than that at pH = 7.4, and its cumulative release rate reaches 74.13%, and then slowly releases over time, and its cumulative release rate reaches more than 90% at 36h. This shows that under acidic conditions, the metal framework ZIF-8 in the composite film is relatively unstable, and the particles will crack, indicating that the material has a strong dependence on the pH of the solution, confirming that ZIF-8@Thy nanoparticles have pH responsiveness. Because ZIF-8 can slowly crack and release bactericidal drugs, and the release time is as long as 36h, this makes the composite film have a long-lasting antibacterial effect.
[0147] (7) MIC (minimum inhibitory concentration)
[0148] MIC refers to the minimum drug concentration required to inhibit bacterial growth under experimental conditions. MIC is usually used to measure the antibacterial ability of antimicrobial agents. The smaller the MIC value, the stronger the antibacterial ability.
[0149] The antibacterial effect of the synthesized composite membrane containing a metal framework on Gram-positive Staphylococcus aureus (ATCC 6538) and Gram-negative Escherichia coli (BNCC336655) was evaluated by measuring the minimum concentration that inhibited the growth of the strain. The concentration gradient of the drug (ZIF-8, Thy, ZIF-8@Thy) was 1024, 512, 256, 128, 64, and 32 μg / mL, and the OD of the cultured bacterial solution was measured by a UV spectrophotometer. 600 =0.5 and then diluted 100 times for later use. Add the prepared drugs and diluted bacterial solution to a 96-well plate (repeat three groups), then place it in a 37°C constant temperature incubator for 12 hours, and measure its absorbance. Due to the presence of bacteria, the test system without antibacterial activity will appear turbid, while the absence of turbidity indicates that the growth of the test bacterial solution is inhibited.
[0150] Result analysis:
[0151] like Figure 8 As shown, the MICs of ZIF-8, Thy and ZIF-8@Thy against Escherichia coli (BNCC336655) were 128 μg / mL, 256 μg / mL and 64 μg / mL, respectively; the MICs of ZIF-8, Thy and ZIF-8@Thy against Staphylococcus aureus (ATCC 6538) were 64 μg / mL, 256 μg / mL and 32 μg / mL, respectively, indicating that the combination of ZIF-8 and Thy enhanced the antibacterial effect of each other and had synergistic antibacterial ability.
[0152] (8) Biosafety test
[0153] L929 fibroblasts were selected as a cell model to evaluate the biocompatibility of the nanofiber membrane. L929 cells were cultured in a DMEM medium containing 10% fetal bovine serum (FBS) and placed in a 37°C constant temperature incubator with 5% CO2. After each group of samples was sterilized by ultraviolet irradiation, an extract with a concentration of 10 mg / mL was prepared using the culture medium, and the extract was extracted at 37°C for 24 hours. The obtained extract was diluted to different experimental concentrations with DMEM culture medium. The experimental concentrations of the composite membrane extract were set to: 0 (control group), 1, 10, 100, 200 μg / mL, and the experimental concentrations of the composite membrane extract were set to: 0 (control group), 25, 50, 100, 200, 400 μg / mL. L929 cells in the logarithmic growth phase were taken, the cells were digested and counted, and the cell concentration was adjusted so that the inoculation density in the 96-well plate was 4×10 3 / well. Treat the cells according to the above extract concentrations and place them in a 37°C constant temperature incubator with 5% CO2 for 24 hours. After the culture, aspirate the original culture medium and wash each well repeatedly with PBS for 3 times, then add 100 μL of culture medium with a volume fraction of 10% CCK-8 to each well and continue to culture in the incubator for 2 hours. Finally, record the absorbance value of each well solution at 450nm and calculate the relative cell viability.
[0154] Result analysis:
[0155] like Fig. 9 As shown in the figure, the κ-carrageenan / Zein / ZIF-8@Thy composite film has good biosafety. Among them, κ-carrageenan is considered safe and reliable for food use by the World Health Organization and the Food and Agriculture Organization of the United States; Zein is listed as a safe (GRAS) material by the U.S. Food and Drug Administration (FDA); Thy has been included in the GRAS food additive list by the European Union (EU) and the U.S. Food and Drug Administration (FDA) and is considered to be a safe and non-toxic antibacterial agent and antioxidant. Zn in ZIF-8 2+ The lethal dose 50 is > 0.35 g / Kg, so ZIF-8 is generally not considered toxic, and the experimental results also confirm this. In Comparative Example 1, the composite membrane formed by non-covalent crosslinking of κ-carrageenan and Zein does not produce toxic substances, and in Comparative Example 2, the composite membrane formed by κ-carrageenan, Zein and ZIF-8 does not produce toxic substances. Therefore, the κ-carrageenan / Zein and κ-carrageenan / Zein / ZIF-8 composite membranes have good biocompatibility, and the κ-carrageenan / Zein / ZIF-8 composite membrane loaded with Thy still has no toxic side effects on L929 fibroblasts.
[0156] (9) Antibacterial test
[0157] The plate count method was used to evaluate the inhibitory effect of the synthesized composite membrane containing a metal frame on bacteria. Bacteria can be mainly divided into Gram-positive (+) and Gram-negative (-), because the structure and composition of bacterial cell membranes are different, which affects their sensitivity to external contents. Here we use Gram-positive Staphylococcus aureus (ATCC 6538) (S. aureus) and Gram-negative Escherichia coli (BNCC336655) (E. coli) to evaluate the antibacterial effect of the composite membrane. After the composite membrane was ground, it was sterilized by ultraviolet light for 30 minutes, and the OD of the cultured bacterial solution was measured by ultraviolet spectrophotometer. 600= 0.5 and then diluted 100 times with liquid culture medium for later use. Dissolve 20 mg of sterilized composite membrane with sterile water, mix with bacterial solution in a test tube at a volume ratio of 1:1, and place in a shaker (200 rpm) for incubation for 2 hours. Dilute the bacterial solution at the end of incubation 1000 times with sterile water, then take 50 μL of the diluted bacterial solution and evenly spread it on the LB plate, incubate it in a 37°C incubator overnight, and calculate the total number of colonies on each plate.
[0158] Result analysis:
[0159] like Fig.10 As shown, the total colony count of the κ-carrageenan / Zein composite film was not significantly different from that of the control group because the polysaccharide and protein had no antibacterial ability; the κ-carrageenan / Zein / ZIF-8 composite film had obvious antibacterial activity against Escherichia coli and Staphylococcus aureus, and the bacterial survival rates were 25.28% and 23.01%, respectively; the antibacterial effect of the κ-carrageenan / Zein / ZIF-8@Thy (30 mg) composite film on Escherichia coli and Staphylococcus aureus was more obvious, and the bacterial survival rates were 15.47% and 0.01%, respectively.
[0160] From the bacterial survival rates of these composite membranes, it can be seen that the antibacterial effect of the κ-carrageenan / Zein / ZIF-8@Thy composite membrane is more excellent, and the antibacterial effect of this composite membrane on Staphylococcus aureus is greater than that on Escherichia coli. This is because Thy, as a natural bactericide, can decompose the outer membrane of microbial cells, promote the release of lipopolysaccharide, induce changes in fatty acid composition and phospholipids, and make the bacterial cytoplasmic membrane permeable and depolarized, leading to the death of bacteria.
[0161] Example 5
[0162] This example provides the use of the κ-carrageenan / Zein / ZIF-8@Thy (30 mg) composite film in Example 1 as a food preservative film.
[0163] Blueberry is a small berry with high economic value, which contains very rich nutrients and has the functions of protecting eyesight, softening blood vessels and enhancing human immunity. However, the preservation of blueberries is more susceptible to environmental influences, which limits their market potential and consumer acceptance. Therefore, κ-carrageenan / Zein / ZIF-8@Thy composite film was used to preserve blueberries, in which κ-carrageenan / Zein composite film and ordinary PVC plastic film were set as comparisons, and the control group was not packaged in order to explore its potential application in food packaging.
[0164] The results are as follows Fig.11As shown in the figure, the blueberries in different packages showed an upward trend during storage due to respiration and transpiration, and the weight loss rate of the control group was significantly higher than that of the packaged group. This is because the moisture of unpackaged blueberries easily evaporates into the air, while the packaging material can prevent the evaporation of blueberry moisture to a certain extent due to its water vapor barrier property. Compared with the control group, the weight loss rate of blueberries packaged with PVC plastic film, κ-carrageenan / Zein composite film and κ-carrageenan / Zein / ZIF-8@Thy composite film was significantly reduced, which is related to the good water vapor barrier property of these films. The weight loss rate of blueberries packaged with κ-carrageenan / Zein / ZIF-8@Thy (30 mg) was significantly lower than that of the PVC plastic film and κ-carrageenan / Zein composite film groups, which is due to the better water vapor barrier property of the above-mentioned κ-carrageenan / Zein / ZIF-8@Thy composite film.
[0165] The detailed description of the preparation method of the ultrasound-assisted κ-carrageenan / Zein / ZIF-8@Thy membrane with pH responsiveness and sustained antibacterial properties and its application with reference to the above-mentioned examples is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.
Claims
1. A κ-carrageenan / Zein / ZIF-8@Thy composite membrane, characterized in that: The main components of the composite film include: kappa-carrageenan, Zein and ZIF-8@Thy.
2. The method for preparing a κ-carrageenan / Zein / ZIF-8@Thy composite film according to claim 1, characterized in that: The method comprises the following steps: S1, dissolving dimethylimidazole and Thy in methanol and stirring until completely dissolved to obtain a dimethylimidazole / Thy solution; S2, dissolving zinc nitrate in methanol and stirring until completely dissolved to obtain a zinc nitrate solution; S3, adding zinc nitrate solution dropwise to dimethylimidazole / Thy solution, stirring for 24-48 hours, collecting precipitate by centrifugation, washing the precipitate with methanol, and vacuum drying to obtain ZIF-8@Thy powder; S4, heating and stirring κ-carrageenan in deionized water until it is completely dissolved to obtain a κ-carrageenan solution; then adding ZIF-8@Thy powder and heating and stirring to make it evenly dispersed, and ultrasonically degassing to obtain a reaction system 1; S5, dissolving Zein in ethanol and stirring until completely dissolved to obtain a Zein solution; S6, adding Zein solution dropwise to the reaction system 1 to obtain the reaction system 2; S7, after ultrasonic degassing, pour the reaction system 2 into a flat plate to obtain a composite system flat plate; S8, drying the composite system plate at 40-60° C. to form a κ-carrageenan / Zein / ZIF-8@Thy composite membrane.
3. The method for preparing a κ-carrageenan / Zein / ZIF-8@Thy composite film according to claim 2, characterized in that: The mass ratio of dimethylimidazole to Thy is 20:1 to 30:1; The mass ratio of the dimethylimidazole to zinc nitrate is 6:1 to 8:
1. The mass ratio of the κ-carrageenan to ZIF-8@Thy is 1:0.5-0.
1. The mass ratio of κ-carrageenan to Zein is 1:0.5-0.
1.
4. The method for preparing a κ-carrageenan / Zein / ZIF-8@Thy composite film according to claim 3, characterized in that: The mass ratio of the κ-carrageenan to ZIF-8@Thy is 1:0.2-0.
1.
5. The method for preparing a κ-carrageenan / Zein / ZIF-8@Thy composite film according to claim 3, characterized in that: The mass ratio of κ-carrageenan to ZIF-8@Thy is 1:0.2, 1:0.15 or 1:0.
1.
6. A method for preparing a κ-carrageenan / Zein / ZIF-8@Thy composite film according to any one of claims 2 to 5, characterized in that: The stirring speed is 500-600 rpm; The ultrasonic degassing is carried out at 35-45KHz for 25-30min; The centrifugal conditions are: centrifugation at 10000-12000 rpm for 10-15 min; The heating and stirring temperature is 40 to 60°C; The standing time is 25 to 30 minutes; The drying time is 12 to 24 hours.
7. The method for preparing a κ-carrageenan / Zein / ZIF-8@Thy composite film according to claim 6, characterized in that: The stirring speed is 600 rpm; The ultrasonic degassing is carried out at 40KHz for 30 minutes; The centrifugation condition is: centrifugation at 12000 rpm for 15 min.
8. Use of the κ-carrageenan / Zein / ZIF-8@Thy composite film according to claim 1 as a food preservative film.
9. Use of the κ-carrageenan / Zein / ZIF-8@Thy composite film according to claim 1 in preparing food preservative film.
